Impact of forest decentralization on sustainable forest management and livelihoods in East Africa - Mekuanent Tebkew; Haimanot B. Atinkut (Trees, Forests and People, 2022)
The paper examines how forest decentralization affects forest management and sustainable livelihoods in East Africa. For this review, Ethiopia, Kenya, Uganda, and Tanzania were chosen as case study nations, and study sites implementing decentralization. We used Google Scholar to find about 280 pieces of peer-reviewed scientific literature. Further, we used the Foucault's approach and the Policy analytical approach (PAA) to distill our review. Finally, we applied assessment indicators: forest conditions, species composition, forest cover, income level, food security status, wealth equality, and equity. Our review of the forest decentralization reforms process based on empowerment and accountability yields the following results: (1) intended to increase efficiency and ecological services are not being implemented properly, (2) forest policy reforms resulted in a net loss of forest area in East Africa, (3) forest status of some forests is stable, and the current decentralization reforms, with the exception of the Duru-Haitemba community-based forest management (Tanzania), do not address the sustainability of the forests. Understandings of the current institutional frameworks and power configurations are insufficient to devolve resources and rights to lower levels of government. This necessitates the development of new viable forest governance systems capable of deviating significantly from established modes of government. Our review suggests that decentralization forest governance and sustainable agricultural resources utilization rely on multilevel institutional architecture, actors’ collaboration at all levels and with regional integration, complement each other to form successful systems within forest landscapes.